Nussbaum's Justice Theory Lens: the Digital Divide and Unfulfillment of the Right to Public Service in Traditional Society - Muh. Afif Mahfud; Siregar, Dzaky Mufrih Aimaluddin; Muhammad Fahad Malik (Universitas Airlangga, 2026)
Economic, social and geographical disparities have led to the emergence of a digital divide between regions, which ultimately has resulted in an inequality of access to public services, which is one of the rights of citizens that must be fulfilled by the government. This study aims to analyze the effect of the digital divide on the inequality of access to digital public services in traditional society specifically. This is as well as the local government strategies ensuring inclusiveness of access and overcoming injustice in public services in terms of Martha Nussbaum's theory of justice. This research is a socio-legal research and interdisciplinary prescriptive study using functional comparative law. Collaboration between local governments and the private sector is a key aspect of facilitating access to public services in areas that are not covered by internet access. The lack of access to digital public services is a form of injustice, is a violation of human rights and relates to the concept of a welfare state. Examined according to Martha Nussbaum's theory of justice, internet access is a fertile capability whose fulfillment determines the fulfillment of fundamental rights in turn (central capabilities). The goal of the rule of law is to create substantive freedom for those in traditional society to develop their lives. This theory places the state as an active entity that must strive to meet the needs of the community regarding digitalization and public services. This research shows that reality has shifted in the context of fulfilling the right to digitalization, which is highly dependent on the private sector, which is not in line with the theory of justice. Therefore, a system change must be made, namely that the development of digitalization must be in line with the expansion and improvement of internet access. The state must take a central role in fulfilling these needs.